DINAMIKA BUDAYA SEKOLAH DALAM PEMBENTUKAN PERILAKU DISIPLIN SISWA DI MTS MAFATIHUL HUDA PUJON MALANG - Yulianto; Zainuddin Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School culture is one of the important factors in shaping students’ character, particularly in fostering disciplined behavior within the educational environment. This study aims to analyze the dynamics of school culture in shaping students' disciplinary behavior at MTs Mafatihul Huda Pujon Malang. The research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students as informants. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that the school culture implemented through habituation activities, school regulations, and routine religious programs was effective in developing students’ disciplinary behavior. The forms of discipline observed included punctuality in attending school, compliance with school rules, discipline in participating in learning activities, and active involvement in religious programs. Teachers played a significant role as role models and mentors in instilling disciplinary values among students. Supporting factors in the development of discipline included the consistent implementation of school culture, teacher support, and continuous habituation activities. Meanwhile, inhibiting factors stemmed from students’ family backgrounds and limited educational facilities and infrastructure. Therefore, a school culture that is consistently implemented and supported by all members of the school community serves as an effective means of fostering disciplined behavior among students at MTs Mafatihul Huda Pujon Malang.